МЕТОДОЛОГІЯ НАУКОВОГО ДОСЛІДЖЕННЯ ОРГАНІЗАЦІЇ ТА ПЛАНУВАННЯ РОЗСЛІДУВАННЯ КРИМІНАЛЬНИХ ПРАВОПОРУШЕНЬ - Татарин, Назарій Миколайович (SUPREMANCE OF LAW, 2019)
The article emphasizes that, taking into account the applied nature of forensic knowledge, the problem of optimization of the pre-trial investigation of criminal offenses is urgent and relevant, in particular, by streamlining it and proper planning. For this purpose, a conceptual analysis of the organization and planning of the investigation of criminal offenses should be carried out. It is argued that in order for such an analysis to be complete, it is necessary to correctly choose the methodology of the corresponding scientific research.